The Effectiveness of the Implementation of Kangaroo Treatment Method in Increasing the Weight Gain of Newborns with LBW - Cicih Nurcholishah; Syatirah Djalaluddin; Fhirastika Annisha Helvian (UNUSA Press, 2022)
Background: Low body weight (LBW) cases have continuously occurred. However, some newborns with LBW could not afford good and hightechnological health services due to several barriers such as cost, geography, transportation, and communication barriers. Incubator replacement through kangaroo treatment method is considered to be an effective and economical alternative in which the weight gain in newborns with LBW could be enhanced. Kangaroo care method can be used in treating newborns with low birth weight. The purpose of this study was to identify the effectiveness of the implementation of the kangaroo care method in increasing the weight gain of newborn with LBW at the General Hospital of Majene. Methods: The research design used in this study was a pre-experiment with One Group Pretest Posttest Design. The sampling method used in this research was total sampling where 38 samples were selected. This research was conducted at the Regional Hospital of Majene in the Perinatology room. Results: The results of this research indicated that there were significant differences in newborns before and after the implementation of the Kangaroo care method. It was evident that the newborns weight significantly increase with the Kangaroo care method. Therefore, further research should be carried out to investigate the factors which influence the increase of newborns weight. Conclusion: In this study we found that there were significant differences in LBW babies before and after being treated with the kangaroo method (PMK).